Analysis of fatigue properties of unmodified and polyethylene terephthalate modified asphalt mixtures using response surface methodology. (December 2015) - Soltani, Mehrtash; Moghaddam, Taher Baghaee; Karim, Mohamed Rehan; Baaj, Hassan
Abstract: Fatigue is a major distress mode of flexible pavements that generally occurs in the form of irregular (alligator) cracking in the wheel paths. This paper evaluates the effects of applied stress and temperature on the fatigue lives of polyethylene terephthalate (PET) modified asphalt mixtures using response surface methodology (RSM). As it is shown in this study a quadratic model is successfully fitted to the experimental data. Fatigue lives of mixtures are influenced by changes in selected parameters. In addition, the effect of temperature variation is more drastic on the fatigue lives than the effects of stress level and modifier content. Highlights: Effect of PET modification on fatigue life of asphalt mixture was examined. Different temperatures and stress levels were designated. Statistical analysis was used to find the interaction between selected variables. A good agreement between experimental results and predicted values was obtained.